Prevalence and Antibiotic Resistance Profiles of Escherichia coli and Staphylococcus aureus in Leafy Vegetables from Open Markets in Abakaliki, Nigeria: Implications for Food Safety and Public Health - Nomeh, Onyinye Lovette; Ogba, Rebecca Chinenye; Kelechi-Mathew, Oluwatosin Oluwatoyin; Christiana, Inuaesiet Edemekong; Ikemesit, Udeme Peter (Journal of Science, Technology and Innovation Research, 2025)
Leafy vegetables are vital component of a healthy diet but can harbor pathogenic bacteria, posing significant public health risks when consumed raw or inadequately washed. This study aimed to isolate and evaluate the antimicrobial resistance profiles of Escherichia coli and Staphylococcus aureus on commonly consumed leafy vegetables from open markets in Abakaliki, Nigeria. Fifteen vegetable samples, including Ugu, Green, Curry, Scent, and Bitter leaf, were analyzed using standard microbiological techniques for bacterial isolation and enumeration of colonies. Escherichia coli and Staphylococcus aureus were identified using the VITEK 2 automated system, while antibiotic susceptibility testing was performed via the Kirby-Bauer disc-diffusion method. The results of colonies enumeration indicated an average counts exceeding 1.3 x 101 CFU/ml and 3.6 x 101 CFU/ml for S. aureus and E. coli respectively. Results of contamination levels, revealed that 60% of the samples were positive for E. coli and 86.7% for S. aureus, including 60% co-contaminated with both pathogens. Escherichia coli exhibited high resistance to Tetracycline (66.7%) and Cotrimoxazole (55.5%) while S. aureus demonstrated significant resistance to Erythromycin (61.5%), Ampicillin, and Cloxacillin (53.9%). Multiple Antibiotic Resistance Index (MARI) values ranges from 0 to 0.6 among isolates. Escherichia coli isolates were susceptible to Gentamicin (100%) while Staphylococcus aureus isolates were susceptible to both Chloramphenicol, and Ciprofloxacin (84.6 %) and Gentamicin 92.3%. Our findings emphasize the urgent need for improved hygiene practices in leafy vegetable handling and stricter regulations to mitigate the prevalence of antibiotic resistance and foodborne disease risks in Abakaliki.